Crystallization by particle attachment in synthetic, biogenic, and geologic environments - De Yoreo, James J.; Gilbert, Pupa U. P. A.; Sommerdijk, Nico A. J. M.; Penn, R. Lee; Whitelam, Stephen; Joester, Derk; Zhang, Hengzhong; Rimer, Jeffrey D.; Navrotsky, Alexandra; Banfield, Jillian F.; Wallace, Adam F.; Michel, F. Marc; et al. (Science (American Association for the Advancement of Science), 2015)
Crystals grow in a number a ways, including pathways involving the assembly of other particles and multi-ion complexes. De Yoreo et al. review the mounting evidence for these nonclassical pathways from new observational and computational techniques, and the thermodynamic basis for these growth mechanisms. Developing predictive models for these crystal growth and nucleation pathways will improve materials synthesis strategies. These approaches will also improve fundamental understanding of natural processes such as biomineralization and trace element cycling in aquatic ecosystems. Science , this issue 10.1126/science.aaa6760 Materials nucleate and grow by the assembly of small particles and multi-ion complexes. Field and laboratory observations show that crystals commonly form by the addition and attachment of particles that range from multi-ion complexes to fully formed nanoparticles. The particles involved in these nonclassical pathways to crystallization are diverse, in contrast to classical models that consider only the addition of monomeric chemical species. We review progress toward understanding crystal growth by particle-attachment processes and show that multiple pathways result from the interplay of free-energy landscapes and reaction dynamics. Much remains unknown about the fundamental aspects, particularly the relationships between solution structure, interfacial forces, and particle motion. Developing a predictive description that connects molecular details to ensemble behavior will require revisiting long-standing interpretations of crystal formation in synthetic systems, biominerals, and patterns of mineralization in natural environments.